UPAYA PENDIDIK MENINGKATKAN PEMAHAMAN KARAKTER PESERTA DIDIK SEKOLAH DASAR ERA 5.0 - Khotimah, Khusnul; Anisa, Nur; Utami, Yugi; Darsono, Darsono (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2024)
This writing describes the efforts of educators to improve the understanding of the character of Elementary School 5.0 students. For pupils, education plays a crucial function in transferring knowledge and developing character. This text employs the literary or literary analysis writing style. This writing data source was compiled using secondary literature, such as books, journals, and scientific articles that are pertinent to the chosen issue. Learning in the 5.0 era can assist students in acquiring the abilities and traits they will need in the real world by fusing technology and novel teaching strategies. Additionally, instructors can develop a holistic learning environment that promotes students' comprehension of the characters by implementing the 5.0 learning strategy. pupils through hands-on learning, teamwork, introspection, and incorporating character values into all facets of learning.